If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10 = x + -12 Reorder the terms: -10 + 2x = x + -12 Reorder the terms: -10 + 2x = -12 + x Solving -10 + 2x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + 2x + -1x = -12 + x + -1x Combine like terms: 2x + -1x = 1x -10 + 1x = -12 + x + -1x Combine like terms: x + -1x = 0 -10 + 1x = -12 + 0 -10 + 1x = -12 Add '10' to each side of the equation. -10 + 10 + 1x = -12 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = -12 + 10 1x = -12 + 10 Combine like terms: -12 + 10 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| -27.5+18.6= | | 3x-6x=21 | | 17x^2-3x-15=0 | | -45=-40t | | 12x+15y=-42 | | 3c-6(2c+6)-4(3c-5)+3c-4= | | 8.2+x=0.7 | | 8h=30 | | (x^2-4x)x=12x | | 15=5v | | 1+4=x-8 | | 2(y+11)+y=19 | | v^2dx+x(v-4x)dv=0 | | 7x=15-8x | | 4x^2-11-20=0 | | 6x+2y=-1 | | p=1+5n-(n-1) | | 7y+72=15y | | 2=4/x | | 3/4x-1/6=2/3 | | 4+8q=5+7q | | -5+7(2x+4)=-9(-7x-4) | | 15n^2+29n-14=0 | | 4*a^2= | | 9n+42=16n | | -4(2x+7)=2x | | 25k^2-25k-14=0 | | -2x+4=-52+6x | | 8a^2+61a+35=0 | | 7x+2-5x=-8+5x-2 | | x+6=-3x-34 | | x/69 |